Sinergi Kebijakan Ekonomi Makro dan Publik dalam Mendorong Peningkatan Hukum Ekonomi Syariah - Ramadhan, Muhammad Nurfaidh; Ani, Yulfi Hari; Fauziah, Neng Siti Karimah; Fauzan, Ahmad; Ramadhan, Fakhziar; Mulkan, Muhammad Rizqi Azis; Zulkipli, Muhammad; Herdiana, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article examines the collaboration mechanism between public economic sector policies and macroeconomics in optimizing the country's economy based on sharia economics. A good understanding of the rules contained in economic policy results in a good economy that has a progressive and accurate nature in accordance with the intention and objectives of the policy is prepared and implemented. Sharia, which is one of the components of the backbone of Indonesian society, plays an important role in this discussion as an object as well as a goal of the synergy of macroeconomic policies and the public economy itself. So that the results of the synergy that occurs are expected to be the spearhead of the country's economy that is fair, transparent, and fulfills the welfare of its people broadly shaded by sharia provisions that have firm principles but are flexible in their application and bring benefits to all groups of society.